Magnitude of second-trimester-induced abortion and associated factors among women who received abortion service at public hospitals of Arba Minch and Wolayita Sodo towns, southern Ethiopia: A cross-sectional study - Abebe, Mesfin; Mersha, Abera; Degefa, Nega; Molla, Wondwosen; Wudneh, Aregahegn (Frontiers in Global Women's Health, 2022)
Abstract Introduction Second-trimester abortion accounts for 10-15% of all induced abortions, with varying rates across countries, and is responsible for two-thirds of major abortion complications. It is also associated with higher medical costs, morbidity and mortality rates than first-trimester. Despite the fact that it is a significant burden, there is a lack of adequate information about second-trimester induced abortion, especially in the study area. As a result, the primary purpose of this study is to fill this research gap, assess the magnitude and associated factors of the second trimester induced abortion in the public hospitals of Arba Minch, and Wolayita Sodo town, Southern Ethiopia. Methods A facility-based cross-sectional study was conducted. Systematic sampling was used to select 353 study participants. Data were collected through face-to-face interviews using a structured questionnaire and record review by using Kobo collect version 3.1. Analysis was done by STATA 14. Logistic regression was used to identify associated factors of the second trimester induced abortion. Results The magnitude of second trimesters induced abortion in the study setting was 23% (95%CI: 18.5%, 27.4%). The factors associated with second trimester induced abortion among women received abortion care services were respondent’s age 25-29 and 30-34years old (AOR=0.38, 95%CI:0.15, 0.96) and (AOR=0.31, 95%CI:0.10, 0.97) respectively, planned pregnancy (AOR=0.22, 95%CI:0.11, 0.44), and delay confirming pregnancy(AOR=2.21, 95%CI:1.15, 4.23). Conclusions This study showed that more than one-fifth of women who presented for abortion care services had second trimesters induced abortion. Health institution organizations working on maternal health at various levels should provide counseling to women to help them early confirm their pregnancy and make decisions about whether or not to continue it as early as possible.